Coming out - Steel, Danielle (Corgi Books, 2007)
All round high-flier Olympia Crawford Rubinstein has it all, a busy legal career, a solid marriage and a perfect family. Until one day she opens an invitation for her twin daughters to attend an exclusive coming out ball and her good fortune is changed irrevocably. Could one calamitous evening ruin the perfect life?